How Coaches Can Improve Their Teams’ Match Performance—The Influence of In-Game Changes of Tactical Formation in Professional Soccer - Forcher, Leon; Forcher, Leander; Jekauc, Darko; Wäsche, Hagen; Woll, Alexander; Gross, Timo; Altmann, Stefan (Frontiers in Psychology, 2022)
The tactical formation has been shown to influence the match performance of professional soccer players. This study aimed to examine the effects of in-game changes in tactical formation on match performance and to analyze coach-specific differences. We investigated three consecutive seasons of an elite team in the German Bundesliga which were managed by three different coaches, respectively. For every season, the formation changes that occurred during games were recorded. The match performance was measured on a team level using the variables ‘goals’, ‘chances’, and ‘last plane’ entries (≙successful attacking sequence) for the own/opposing team. Non-parametric tests were used to compare the ten minutes before with the ten minutes after the formation change, as well as games with and without formation change. In the ten minutes after the formation change, the team achieved more goals/chances/last plane entries than in the ten minutes before the formation change (mean ES=0.52). Similarly, the team conceded fewer opposing goals/chances/last plane entries in the ten minutes after the formation change (mean ES=0.35). Furthermore, the results indicate that the success of the respective formation change was dependent on the responsible coach. Depending on the season, the extent of the impacts varied (season 1: mean ES=0.71; season 2: mean ES=0.26; season 3: mean ES=0.22). Over all three seasons, the formation changes had a positive effect on the match performance of the analyzed team, highlighting their importance in professional soccer. Depending on the season, formation changes had varying impacts on the performance, indicating coach-specific differences. The provided information can support coaches in understanding the effects of their in-game decisions.